Acceptable Lifestyle Intervention Telerehabilitation (Lita): Cardiac Rehabilitation Based Android - Lita, Lita (STIKes Alifah Padang, 2023)
Coronary artery disease (CAD) is a collection of acute coronary syndromes caused by plaque buildup in the heart's coronary arteries. CAD can reduce the quality of life for sufferers-efforts to improve the quality of life of CAD with cardiac rehabilitation. The development of current technology to overcome transportation barriers, distance, and difficulties in accessing health services in rehabilitation is by utilizing an Android-based cardiac telerehabilitation application. This study aimed to identify the use of Android-based cardiac rehabilitation applications in coronary heart disease patients. This research is a descriptive study using a survey approach. The number of samples is 30 people. This study used the System Usability Scale (SUS) questionnaire. The analysis used is univariate analysis using descriptive tests and central tendency. Based on the results of the study, it was found that the average age of the respondents was 57 years, the most gender was male 23 people (76.7%), the last education was high school 11 people (36.7%), the most jobs were self-employed as many as eight people (26.7%), and the test results The distribution of the frequency of using an Android-based cardiac rehabilitation application shows that 19 people (63.3%) choose the acceptable option. It was concluded that Android-based cardiac rehabilitation applications were acceptable and used in facilitating cardiac rehabilitation. Hopefully, this research can be an intervention given to patients to make it easier to undergo cardiac rehabilitation independently at home.